Un sensore aviotrasportato per analisi immagini a supporto degli incendi - Laneve, Giovanni; Bueno Morles, Ramon; Pampanoni, Valerio (GEOmedia, 2023)
This contribution describes the creation of a support system for the operational activities of detailed perimeter of wooded areas attacked by insects/pathogens and/or forest fires, by means of a SAPR (Airborne System with Remote Piloting) with definition of the trajectory in automation via realtime recognition assisted by an airborne sensor and satellite system.